2018
DOI: 10.3791/58486
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Imaging of Single Proteins Secreted from Living Cells via iSCAT Microscopy

Abstract: We demonstrate interferometric scattering (iSCAT) microscopy, a method capable of detecting single unlabeled proteins secreted from individual living cells in real time. In this protocol, we cover the fundamental steps to realize an iSCAT microscope and complement it with additional imaging channels to monitor the viability of a cell under study. Following this, we use the method for real-time detection of single proteins as they are secreted from a living cell which we demonstrate with an immortalized B-cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Nevertheless, lateral vibrations might compromise ultrasensitive measurements because even a few nanometers of motion suffice to change the differential contrast that results from imperfect background subtraction. 27…”
Section: Interferometric Scattering (Iscat) Detectionmentioning
confidence: 99%
“…Nevertheless, lateral vibrations might compromise ultrasensitive measurements because even a few nanometers of motion suffice to change the differential contrast that results from imperfect background subtraction. 27…”
Section: Interferometric Scattering (Iscat) Detectionmentioning
confidence: 99%
“…18 The interference between the scattered and reflected light enhances sensitivity by producing a signal that scales linearly with particle polarizability, which may be interpreted as mass for objects with fixed composition. 1921 Our initial study demonstrated trapping of gold nanoparticles as small as 20 nm, and that polymer nanoparticles down to 50 nm diameter could be held for more than 30 seconds. Fluorescently labeled particles could also be trapped far beyond the time of photobleaching.…”
Section: Main Textmentioning
confidence: 95%
“…3). Nevertheless, lateral vibrations might cause problems since even a few nanometers of motion could translate into fluctuations of the contrast when the background is subtracted (see section below) [135].…”
Section: Detection Sensitivity and Signal-to-noise Ratio (Snr)mentioning
confidence: 99%
“…Another recent application of label-free single-protein detection was showcased in the context of real-time investigation of cellular secretion [135,166], shown in Fig. 12c.…”
Section: Proteinsmentioning
confidence: 99%